If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M + -9 = -17 Reorder the terms: -9 + M = -17 Solving -9 + M = -17 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + M = -17 + 9 Combine like terms: -9 + 9 = 0 0 + M = -17 + 9 M = -17 + 9 Combine like terms: -17 + 9 = -8 M = -8 Simplifying M = -8
| 59/100= | | Y-14=21 | | X+80=(1.3X)+15 | | -19+46= | | X+80=(1.2X)+15 | | 2=5n-3 | | y-4=-4/7(x--2) | | -5(1-7)=-110 | | V+-9=14 | | X+80=(2(1.1X))+15 | | X+80=(1.1X)+15 | | x^3-7x^2+15x+9=0 | | 4-2(-2x+2)=4x+2 | | -1/2(7x-28) | | 6x+9=x+6 | | 9p-12=8p | | x-50.5=-16.9 | | 9(1+4n)=-279 | | 4-11b=15 | | 1/z=12/10z-8 | | g-9/9=4/9 | | 3y-5d=5d-4 | | 13+3s=-47 | | 6r+27=30 | | (x-2)(3x-12)=0 | | k-8/2=12 | | 13/8m=1/2 | | -5/2*=34 | | -2m/3=-12 | | 5(x+20)=3x+180 | | 3a-8=-6+8 | | 22=6c |